Airline passengers’ continuance intention towards online check-in services: The role of personal innovativeness and subjective knowledge - Lin, Zhibin; Filieri, Raffaele (Transportation research. Part E, Logistics and transportation review, 2015)
•Two psychological factors are integrated into TAM to predict continuance intention.•Both personal innovativeness and subjective knowledge are significant predictors.•Personal innovativeness also has an indirect effect on continuance intention. This study integrates the individual psychology constructs (personal innovativeness and subjective knowledge) with the Technology Acceptance Model to develop and test a model of airline passengers’ continuance intention towards online flight check-in services. Predictions were tested with data from a sample of airline passengers in China who have experienced the online check-in service. The findings of this study demonstrate that airline passengers’ innovativeness and subjective knowledge have a direct effect on continuance intention, and an indirect effect through partial mediation of perceived ease of use and perceived usefulness. Theoretical and managerial implications are discussed.